Draft animal power for Vertisol management - Astatke, A.; Mohamed-Saleem, M.A. (Ethiopian Agricultural Research Organization, 2001)
This chapter discusses the traditional tillage implement and the alternative tillage implements using animal power in Vertisol management. Among the topics of discussion are land shaping equipment; the ridge and furrow system; minimum tillage with BBM attachments; animal drawn scoops; pond excavation using animal power; other land formation equipment, and water lifting equipment.